2011
DOI: 10.4269/ajtmh.2011.10-0685
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis among Young Children in Usoma, Kenya

Abstract: Abstract. Although schistosomiasis burden is greatest among school-age children (SAC) (6-15 years of age), infection among preschool-age children (PSAC) (1-5 years), may be underestimated in endemic areas. We conducted a crosssectional study evaluating Schistosoma mansoni infection among children 1-15 years of age in a highly endemic community in Kenya. Diagnostic tests included stool exam (Kato/Katz technique), serum testing for schistosome-specific antibodies, and urine testing for circulating cathodic antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 21 publications
6
63
3
1
Order By: Relevance
“…Schistosoma mansoni and STH prevalence in our study sample were high and comparable to levels found in other studies of similarly aged children in areas where praziquantel MDA has not been implemented 5,6,23 ; although infection intensity is not a direct indicator of morbidity, its consistent association with disease consequences and easily quantified outcomes maintain its use in monitoring program impact.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Schistosoma mansoni and STH prevalence in our study sample were high and comparable to levels found in other studies of similarly aged children in areas where praziquantel MDA has not been implemented 5,6,23 ; although infection intensity is not a direct indicator of morbidity, its consistent association with disease consequences and easily quantified outcomes maintain its use in monitoring program impact.…”
Section: Discussionsupporting
confidence: 53%
“…5,32 The positive association between S. mansoni and P. falciparum infections has been found in many studies 5,33,34 and may be driven by immunologic factors. [35][36][37] Anemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 With more sensitive testing, there is greater evidence that Schistosoma infection begins in very early childhood. [15][16][17] While children under 5 years are not yet included in WHO preventive chemotherapy protocols, 18 anti-schistosomal treatment with praziquantel for preschool children could be easily synergized with the ongoing STH early childhood strategies for the prevention of anemia. 18 The aim of this study was to use more in-depth laboratory testing to identify the most likely mechanisms for anemia among children in a resource-limited area endemic for multiple chronic parasitic infections, with the goal of informing local and regional choices for management of early childhood anemias.…”
Section: Introductionmentioning
confidence: 99%